Web-based mindfulness (interactive video) intervention design on depression and quality of life in haemodialysis patients: A randomised control trial - Syamsiah, Nita; Nurjanah, Uun; Erlena, Erlena (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: Patients undergoing hemodialysis (HD) tend to experience higher levels of depression and decreased quality of life (QoL) compared to the general population. Web-based mindfulness intervention using interactive video is an innovative approach that can help HD patients cope with stress and improve their quality of life. This technology allows patients to perform mindfulness exercises independently and in a directed manner. Purpose: To design a web-based mindfulness intervention (interactive video) on depression levels and quality of life in hemodialysis patients. Method: A randomized controlled trial (RCT) study to compare the effectiveness of a web-based mindfulness intervention by measuring depression levels and quality of life. The population in this study were patients undergoing hemodialysis therapy at Karawang Hospital with random sampling that would be divided into intervention and control groups, carried out for 8 weeks and evaluated three times. Results: There was a significant decrease in depression levels in the intervention group from 48.51 (SD = 15.22) in the pre-test to 40.78 (SD = 19.42) in the post-test with a t-value of 9.39 and a p-value of 0.001. While in the control group there was no significant decrease in the pre-test (50.32 ± 16.82) and post-test (49.20±17.66) with a value of 5 of 2.87 and a p-value of 0.435. Likewise in the intervention group there was a significant increase in quality of life from 70.20 (SD = 33.66) in the pre-test to 78.56 (SD = 39.87) in the post-test with a t-value of 10.04 and a p-value of 0.001. Meanwhile, in the control group, there was no significant increase between the pre-test (69.48 ± 22.60) and post-test (67.41 ± 21.83) with a t-value of -4.87 and a p-value of 0.063. Conclusion: There is no correlation between demographic characteristics with depression and quality of life in patients undergoing hemodialysis, except for the variables of duration of hemodialysis and number of comorbidities. In the intervention group, there was a decrease in depression levels and an increase in quality of life post-intervention. While in the control group, there was no significant decrease in depression levels and an increase in quality of life. Suggestion: Further research is needed to evaluate the effectiveness of web-based mindfulness interventions against existing interventions, such as cognitive behavioral therapy, meaning-centered group psychotherapy, acceptance therapy, and commitment in hemodialysis patients. Keywords: Depression; Hemodialysis; Interactive Video; Mindfulness; Quality of Life. Pendahuluan: Pasien yang menjalani hemodialisis (HD) cenderung mengalami tingkat depresi yang lebih tinggi dan penurunan kualitas hidup (Quality of Life/QoL) dibandingkan populasi umum. Intervensi mindfulness berbasis web menggunakan video interaktif menjadi pendekatan inovatif yang dapat membantu pasien HD mengatasi stres dan meningkatkan kualitas hidup. Teknologi ini memungkinkan pasien untuk melakukan latihan mindfulness secara mandiri dan terarah. Tujuan: Untuk merancang intervensi mindfulness berbasis web (video interaktif) terhadap tingkat depresi dan quality of life pada pasien hemodialisa. Metode: Penelitian randomized control trial (RCT) untuk membandingkan keefektifan intervensi mindfulness berbasis web dengan mengukur tingkat depresi dan kualitas hidup. Populasi pada penelitian ini adalah pasien yang menjalankan terapi hemodialisa di RSUD Karawang dengan pengambilan sampel secara acak yang akan dibagi menjadi kelompok intervensi dan kontrol, dilakukan selama 8 minggu dan dievaluasi sebanyak tiga kali. Hasil: Terjadi penurunan yang signifikan tingkat depresi pada kelompok intervensi dari 48.51 (SD=15.22) ketika pre-test menjadi 40.78 (SD=19.42) ketika post-test dengan t sebesar 9.39, dan p-value 0.001. Sementara pada kelompok kontrol, tidak ada penurunan yang signifikan ketika pre-test (50.32 ±16.82 dan ketika post-test (49.20 ± 17.66) dengan nilai 5 sebesar 2.87 dan p-value 0.435. Begitu pula terjadi peningkatan kualitas hidup secara signifikan dari 70.20 (SD=33.66) ketika pre-test menjadi 78.56 (SD=39.87) ketika post-test dengan nilai t sebesar 10.04 dan p-value 0.001 pada kelompok intervensi. Sementara pada kelompok kontrol tidak ada peningkatan yang signifikan antara pre-test (69.48±22.60) dan post-test (67.41±21.83) dengan nilai t sebesar -4.87 dan p-value 0.063. Simpulan: Tidak ditemukan korelasi antara karakteristik demografis dengan depresi dan kualitas hidup pada pasien yang mengalami hemodialisis, kecuali variabel lama menderita hemodialisis dan jumlah komorbiditas. Pada kelompok intervensi, terjadi penurunan tingkat depresi dan kualitas hidup meningkat setelah intervensi. Sementara pada kelompok kontrol, tidak ada penurunan tingkat depresi dan peningkatan kualitas hidup yang signifikan. Saran: Penelitian lebih lanjut harus dilakukan untuk mengevaluasi efektivitas intervensi mindfulness berbasis web terhadap intervensi yang sudah mapan, seperti terapi perilaku kognitif, psikoterapi kelompok yang berpusat pada makna, terapi penerimaan, dan komitmen pada pasien dengan hemodialisis. Kata Kunci: Depresi; Hemodialisa; Mindfulness; Quality of Life; Video Interaktif.